Entity linking and API resource-based matchmaking for Web APIs composition - Boustil, Amel; Tabet, Youcef (Service oriented computing and applications, 2023)
Web APIs composition is still a challenging task. In the classical semantic composition approach, the matchmaking process uses ontologies to ensure semantic matching between inputs and outputs. In this paper, we address the composition of Web APIs based on entity linking of Web APIs to a given knowledge base (KB). We first consider the APIs resources that make up the main core of REST Web APIs. Then, we link both the API resource described in the OAS (Open API Specification) documents and the input/output attributes of Web API operations to entities of the given KB. Finally, we perform discovery and composition of Web APIs based on their related entities extracted from the KB. Our dependency graph realizes matchmaking based on identifying similar entities of the API resources and the attributes of the requested input and output parameters. Focusing on API resources reduces the space of searching for candidate operations. Moreover, extending the user query by related similar entities adds semantics to the matchmaking process in the KB context. Experiments on the developed prototype show the feasibility and the scalability of our proposed composition approach.